Nature versus the army of Ivan Paskiewicz during a expedition to Hungary in 1849 - Kita, Jarosław (Armia kontra natura, 2020)
In June 1849, the Russian intervention army under the command of Field Marshal Ivan Paskiewicz entered Hungary to provide support to the Austrian army. Several thousand Poles fought on the Hungarian side and some of them left diaries regarding the events of the Hungarian Spring of Nations. In turn, Poles also served in the Russian army, but we know very little of the documentaries created by them. Therefore, it is an interesting and little used source. In this text, based primarily on the memories of participants in the fighting in Hungary in 1849, historical reflection was taken on the problem to what extent nature influenced the activities carried out by the tsarist army. The authors of the memoirs did not write much about it, and if they already addressed this problem, they pointed to two main issues, namely the prevailing heat and the spreading cholera epidemic. In addition, some problems, although probably not the most important for memoirists, were crossing large rivers, such as the Cisa and long marches without food and water.